Sistema de armazenamento de energia elétrica gerada por Pavement Energy Harvesting para carregamento de veículos elétricos - Tiago André Martins Barbosa (2021)
Pavnext is a startup that aims to develop energy generation and storage solutions in a sustainable way. The NEXT-Road product, currently being developed, converts kinetic energy from the deceleration of cars into electricity. Vehicles reduce their speed by about 40% when passing through the system, without the need for braking by the driver, and with minimal impact on the comfort of car occupants. In addition, this system allows the collection of relevant vehicle data, which will then be stored in the cloud. The energy from the deceleration of cars can be used for the lighting of local roads and walkways, power of the public network, or charging of small electric vehicles, such as scooters and bicycles, the latter being the focus of the dissertation. Firstly, a brief analysis of the next-road power generation process was carried out. Next, a survey of the characteristics of the electric vehicles available on the market was made in order to understand the needs of the system. Subsequently, studies were carried out on energy storage technologies and power electronics circuits, as well as the market offering of microcontrollers and human-machine interfaces, and programs for project development. Several simulations were carried out in order to design the energy control and regulation systems between ultracapacitors and a lithium-ion battery, followed by their experimental validation. In addition, a boost converter has been designed to validate the system concept, as well as an API to monitor all constituent subsystems. Finally, PCBs of the various subsystems were developed, along with a final validation of the complete system.